Why do psychiatric patients have higher cancer mortality rates when cancer incidence is the same or lower?. (March 2016) - Kisely, Steve; Forsyth, Simon; Lawrence, David
Objective: Studies of overall cancer incidence and mortality in psychiatric patients have had mixed results. Some have reported lower than expected cancer incidence or mortality, while others have found no association or an increased risk depending on sample, psychiatric diagnosis, cancer site and methodology. Few studies have compared cancer incidence and mortality using the same population and methodology. Method: A population-based record-linkage analysis to compare cancer incidence and mortality in psychiatric patients with that for the general Queensland population, using an historical cohort to calculate age- and sex-standardised rate ratios and hazard ratios. Mental health records were linked with cancer registrations and death records from 2002 to 2007. Results: There were 89, 992 new cancer cases, of which 3349 occurred in people with mental illness. Cancer incidence was the same as the general population for most psychiatric disorders. Rates were actually lower for dementia (hazard ratio = 0.77; 95% confidence interval = [0.67, 0.88]) and schizophrenia (hazard ratio = 0.84; 95% confidence interval = [0.72, 0.98]). By contrast, mortality was increased in psychiatric patients (hazard ratio = 2.27; 95% confidence interval = [2.15, 2.39]) with elevated hazard ratios for all the main psychiatric diagnoses. Conclusions: Lifestyle, such as alcohol or tobacco use, would not explain our findings that people with mental illness are no more likely than the general population to develop cancer but more likely to die of it. Other factors may be the difficulty in differentiating medically explained and unexplained symptoms, greater case fatality or inequity in access to specialist procedures. The study highlights the need for improved cancer screening, detection and intervention in this population.